Pacific Realities : Changing Perspectives on Resilience and Resistance. - Dousset, Laurent (Pacific Perspectives: Studies of the European Society for Oceanists Ser., 2018)
Throughout the Pacific region, people are faced with dramatic changes, often described as processes of "glocalization"; individuals and groups espouse multilayered forms of identity, in which global modes of thinking and doing are embedded in renewed perceptions of local or regional specificities. Consequently, new forms of resistance and resilience - the processes by which communities attempt to regain their original social, political, and economic status and structure after disruption or displacement - emerge. Through case studies from across the Pacific which transcend the conventional "local-global" dichotomy, this volume aims to explore these complex and interwoven phenomena from a new perspective.